miR-214-5p Regulating Differentiation of Intramuscular Preadipocytes in Goats via Targeting KLF12 - Du, Yu; Wang, Yong; Li, Yanyan; Emu, Quzhe; Zhu, Jiangjiang; Lin, Yaqiu (Frontiers in Genetics, 2021)
Intramuscular fat (i.m.) is an adipose tissue that is deposited between muscle bundles. An important type of post-transcriptional regulatory factor, miRNAs, has been observed as an important regulator that can regulate gene expression and cell differentiation through specific binding with target genes, which is the pivotal way determining intramuscular fat deposition. Thus, this study intends to use RT-PCR, cell culture, liposome transfection, real-time fluorescent quantitative PCR (qPCR), dual luciferase reporter systems, and other biological methods clarifying the possible mechanisms on goat intramuscular preadipocyte differentiation that is regulated by miR-214-5p. Ultimately, our results showed that the expression level of miR-214-5p peaked at 48 h after the goat intramuscular preadipocytes were induced for adipogenesis. Furthermore, after inhibition of the expression of miR-214-5p, the accumulation of lipid droplets and adipocyte differentiation in goat intramuscular adipocytes were promoted by the way of up-regulation of the expression level of lipoprotein lipase (LPL) (p < 0.05) and peroxisome proliferator-activated receptor gamma (PPARγ) (p < 0.01) but inhibited the expression of hormone-sensitive lipase (HSL) (p < 0.01). Subsequently, our study confirmed that Krüppel-like factor 12 (KLF12) was the target gene of miR-214-5p. Inhibition of the expression of KLF12 promoted adipocyte differentiation and lipid accumulation by upregulation of the expression of LPL and CCAAT/enhancer binding protein (C/EBPα) (p < 0.01). Overall, these results indicated that miR-214-5p and its target gene KLF12 were negative regulators in progression of goat preadipocyte differentiation. Our research results provided an experimental basis for finally revealing the mechanism of miR-214-5p in adipocytes.